2006
DOI: 10.1111/j.1440-1819.2006.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress buffering effects of social support on depressive symptoms in middle age: Reciprocity and community mental health

Abstract: Little is known about the association between depression and the buffering effects of social support in mid-life crisis. The aim of this study is to determine the buffering effects of social support on depression concerning middle-aged individuals, while also taking reciprocity and gender differences into careful consideration. A cross-sectional survey of all middle-aged individuals (40-69 years of age) using a large sample (n = 4558) from a community-living population, who resided in Rokunohe town, Aomori pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 46 publications
(73 reference statements)
7
64
0
Order By: Relevance
“…Although mean scores of failed reciprocity from partner and general trust were higher in women than in men, we did not observe gender-specific differences in the strength of association with health. Previous reports found gender differences with regard to health effects of providing and receiving support [23][24][25]. For instance, in a Finnish prospective study, giving more support than receiving was beneficial for health among women, whereas in men, the reversed effect was found [23].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although mean scores of failed reciprocity from partner and general trust were higher in women than in men, we did not observe gender-specific differences in the strength of association with health. Previous reports found gender differences with regard to health effects of providing and receiving support [23][24][25]. For instance, in a Finnish prospective study, giving more support than receiving was beneficial for health among women, whereas in men, the reversed effect was found [23].…”
Section: Discussionmentioning
confidence: 97%
“…Investigating the potential confounding role of negative social support is of primary importance, as nonreciprocal close relations and negative social support may measure distinct but overlapping concepts that may affect health independently of each other. So far, there is limited evidence available for each one of these associations [19][20][21][22][23][24][25]. Yet, to our knowledge, no previous investigation has explored their separate effects in a single data set.…”
Section: Introductionmentioning
confidence: 96%
“…Longitudinal studies have shown that older adults who feel useless to others are more likely than those who feel useful to others to experience an increase in disability or to die [4][5][6][7] . In a middle-aged community-living population, the stress-buffering effect on depressive symptoms of providing support was demonstrated for males, but not for females, indicating a gender difference 8) . However, whether feeling useful to others plays an important role in health in the workplace, has not yet been clarified.…”
mentioning
confidence: 83%
“…Friends and family members may provide important resources, such as, assistance in finding employment, help accessing legal and economic support, and may influence individual's engagement with health protective behaviors (e.g. vaccinations or preventive screening) that impacts overall health [37,38]. However, not all social connections are beneficial.…”
Section: Conceptual Frameworkmentioning
confidence: 98%